AI-Based Genre Classification and Recommendation System for Nepali Music - Baral, Hari Prasad (OODBODHAN, 2025)
The music industry has experienced significant evolution with the emergence of digital technologies, especially through streaming platforms that have transformed how music is created, distributed, and consumed. As internet usage expands, music remains an essential aspect of daily life. Over the past three decades, traditional methods of discovering and listening to music have shifted drastically. Streaming services now provide instant access to vast music libraries, making them the preferred medium for listeners globally. This research project, Nepali Music Type Analysis and Recommendation, seeks to develop a Nepali-focused music streaming platform that enhances user engagement through intelligent music classification and personalized song recommendations. By leveraging machine learning to analyze user behavior and song attributes such as genre and style, the system aims to deliver customized music suggestions. In doing so, it not only improves music discoverability but also supports and promotes local Nepali artists through an intuitive and user-friendly platform.